Description of community motivation in Palopo about excercising during COVID-19 - Firmansyah Dahlan; Nasriandi; Ahmad (UIR Press, 2022)
A person's willingness to exercise is strongly influenced by motivation. The purpose of this research is to discover The description of the people’s motivation in doing physical activity during COVID-19 pandemic based on the social stratification and the motivation indiccators (intrinsic & extrinsic). The research method uses descriptive analysis. The determination of the sample uses Quota Sampling which amounts to 1% of the total population, namely 1,389 people. The data collection technique uses a questionnaire which is divided into 18 questions with the help of the google form application. The research time is July–August 2021, where the research follows the provisions of WFH (work from home). Data analysis techniques using Microsoft Excel and SPSS 20 applications. The results, people’s motivation in doing physical activity during COVID-19 Pandemic is based on the social stratification, majority are on the very high category. We hope that the results of this research can be a scientific reference for policy makers, relevant agencies, sports practitioners, in drafting regulations related to community physical activity (exercise) during the COVID 19 Pandemic. Limitations of research and suggestions for further research; There is a possibility of bias when respondents answered the questionnaire, considering the very long period of the COVID-19 pandemic in Indonesia and various phases such as Lockdown/Large-Scale Restrictions (PSBB), Small/limited scale restrictions, and New Normal (Adaptation of new habits).In the future, Similar research should include the phase and or time (date/year) so that there is no bias when respondents answer the questionnaire and should collaborate with more credible government agencies if involving a wider sample.